2004
DOI: 10.1103/physreve.70.036405
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of proton and heavier ion acceleration in ultrahigh-intensity laser interactions with heated target foils

Abstract: Proton and heavy ion acceleration in ultrahigh intensity ( approximately 2 x 10(20) W cm(-2) ) laser plasma interactions has been investigated using the new petawatt arm of the VULCAN laser. Nuclear activation techniques have been applied to make the first spatially integrated measurements of both proton and heavy ion acceleration from the same laser shots with heated and unheated Fe foil targets. Fe ions with energies greater than 10 MeV per nucleon have been observed. Effects of target heating on the acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(49 citation statements)
references
References 14 publications
0
49
0
Order By: Relevance
“…Because of the presence of hydrocarbon and water vapour on the surfaces of the foils (for experiments performed at typical vacuums of approximately 10 K5 mbar), protons are usually observed in large numbers, and due to their high charge-to-mass ratio they are more efficiently accelerated than heavier ion species and effectively screen the electric acceleration fields experienced by heavier ions. Recent studies have shown that in order to efficiently accelerate heavier ions the proton source layers should be removed from the target foil by heating or ablation (Hegelich et al 2002;McKenna et al 2004). In addition to ion acceleration in the forward direction (direction of laser propagation), we note that plasma expansion at the front surface of the target foil can also lead to ion acceleration in the backward direction.…”
Section: Ion Acceleration Mechanismsmentioning
confidence: 99%
“…Because of the presence of hydrocarbon and water vapour on the surfaces of the foils (for experiments performed at typical vacuums of approximately 10 K5 mbar), protons are usually observed in large numbers, and due to their high charge-to-mass ratio they are more efficiently accelerated than heavier ion species and effectively screen the electric acceleration fields experienced by heavier ions. Recent studies have shown that in order to efficiently accelerate heavier ions the proton source layers should be removed from the target foil by heating or ablation (Hegelich et al 2002;McKenna et al 2004). In addition to ion acceleration in the forward direction (direction of laser propagation), we note that plasma expansion at the front surface of the target foil can also lead to ion acceleration in the backward direction.…”
Section: Ion Acceleration Mechanismsmentioning
confidence: 99%
“…All these data concern backLaser-driven generation of fast particles ward-emitted ion beams [10,45,47,50,59], as the parameters of forward-emitted beams (produced by TNSA) measured up to now were lower [37]. We can note that the highest ion charge states were achieved with long-pulse lasers [10] in spite of the fact that the laser intensity produced by these lasers (~10 15 -10 16 W/cm 2 ) was significantly lower than in the short-pulse case (up to 5´10 19 W/cm 2 ).…”
Section: Generation Of Highly Charged Heavy Ion Beamsmentioning
confidence: 99%
“…In fact, these nuclear reactions were used for the proton beam diagnostic in many experiments Snavely et al 2000;McKenna et al 2004;Clarke et al 2008). Another possible application of the nuclear reactions induced by laser-driven proton beams is the thin layer activation (TLA) (Racolta et al 1995), which allows studying the wear of tools, for example cutting tools made from cubic boron nitride (BN) or artificial polycrystalline diamond (DIA) (Conlon 1985;Vasváry et al 1994).…”
Section: Radioactivation Experimentsmentioning
confidence: 99%